The Effect of Achilles Tendon Loading on Ankle Joint Contact Area and Peak Pressure. Issue 3 (14th September 2018) - Latt, L. Daniel; Ayala, Alfonso; Kim, Samuel; Lopez, Jesus
Category: Ankle Introduction/Purpose: Increased tibiotalar peak pressure (PP) and decreased contact area (CA) following ankle fracture are associated with the development of post-traumatic osteoarthtritis. Lateral talar translation of just 1 mm has been shown to decrease CA by 42%. The impact of talar malalignment in other directions on ankle joint contact pressures (AJCP) are not well understood. The majority of research on AJCP has utilized cadaveric models in which body weight is simulated with an axial load applied through the tibia. This model does not account for Achilles tendon - which transmits the largest tendon force in the body during weight bearing. This study aimed to determine the effects of Achilles tendon loading on tibiotalar CA and PP in an axially loaded cadaver model at different ankle flexion angles. Methods: Ten fresh frozen cadaveric lower extremity specimens transected mid-tibia were dissected free of soft tissues surrounding the ankle, sparing the ligaments. The proximal tibia and fibula were potted in quick drying cement for rigid mounting on a MTS machine. A pressure sensing element (TekScan KScan model 5033) was inserted into the tibiotalar joint and used to measure CA (cm2) and PP (MPa). An axial load of 686 N was applied through the tibia and fibula, followed by a 350 N load via the Achilles tendon to simulate mid-stance conditions. Measurements were taken at neutral position, 15 degrees of dorsiflexion and 15 degrees of plantarflexion, with and without Achilles load. The effects of Achilles load and ankle flexion angle on CA and PP were analyzed using a 2x3 ANOVA. Bonferroni post-hoc adjustments were used for multiple comparisons. Level of statistical significance was set at p < 0.05. Results: ANOVA revealed significant main effects of ankle flexion on contact area and peak pressures (Table 1). Contact area was significantly lower for 15 degrees of plantarflexion than neutral and 15 degrees of dorsiflexion (p < 0.001). In addition, peak pressure was significantly higher for 15 degrees of plantarflexion than neutral and 15 degrees of dorsiflexion. ANOVA also indicated that contact area and peak pressure were significantly higher with Achilles load than without (p < 0.001). No interaction effects were found. Conclusion: The applied Achilles tendon load significantly altered tibiotalar PP in an axially loaded cadaver model. On the other hand, changes in CA with Achilles load were found to be minimal ( 1.8%). We also found that the greatest PP and smallest CA occured during plantar flexion. This observation can be explained by a difference in width between the anterior and posterior talus. While the results of this study demonstrate the importance of Achilles tendon load on tibiotalar measurements, further studies investigating the effects of additional factors such as loading techniques are warranted to improve the physiological accuracy of cadaver models.